2016
DOI: 10.1186/s12936-016-1252-3
|View full text |Cite
|
Sign up to set email alerts
|

Key traveller groups of relevance to spatial malaria transmission: a survey of movement patterns in four sub-Saharan African countries

Abstract: BackgroundAs malaria prevalence declines in many parts of the world due to widescale control efforts and as drug-resistant parasites begin to emerge, a quantitative understanding of human movement is becoming increasingly relevant to malaria control. However, despite its importance, significant knowledge gaps remain regarding human movement, particularly in sub-Saharan Africa.MethodsA quantitative survey of human movement patterns was conducted in four countries in sub-Saharan Africa: Mali, Burkina Faso, Zambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 27 publications
3
66
1
Order By: Relevance
“…While the migration rate in scenario 12 is likely to be much higher than the true migration rate, this scenario demonstrates that outcome of an elimination program is highly dependent on the nature and extent of regional human movement. While efforts are beginning to be made to characterize relevant human migration patterns [2224], understanding local geographies and conditions will ultimately be crucial for predicting whether an elimination program will succeed.…”
Section: Resultsmentioning
confidence: 99%
“…While the migration rate in scenario 12 is likely to be much higher than the true migration rate, this scenario demonstrates that outcome of an elimination program is highly dependent on the nature and extent of regional human movement. While efforts are beginning to be made to characterize relevant human migration patterns [2224], understanding local geographies and conditions will ultimately be crucial for predicting whether an elimination program will succeed.…”
Section: Resultsmentioning
confidence: 99%
“…In sub-Saharan Africa, a recent survey in Mali, Burkina Faso, Zambia, and Tanzania [11] found that women traveling with children are a remarkably consistent group of travelers of relevance to malaria transmission ( Figure 1B). While this group is more likely to own a bed net in some countries, they are significantly more likely to travel to areas of high malaria prevalence in all countries surveyed.…”
Section: Key Traveler Groupsmentioning
confidence: 95%
“…Census-derived migratory movements have been shown to correlate with CDR-derived short-term movements in Mesoamerica, suggesting that census data could serve as a predictor for human movement at multiple scales [10]. Furthermore, detailed surveys recording movement patterns, demographic data, and cell phone usage behavior can help to correct for biases inherent in these data sets and to classify traveler groups with distinct malaria risk characteristics [11]. Each of these data sets is associated with its own biases and a research agenda is needed to understand those biases and prioritize surveillance protocols that will be operationally useful.…”
Section: Surveillance Of Humans and Parasitesmentioning
confidence: 99%
See 2 more Smart Citations